Persistent organic pollutants exposure assessment using the US Total Diet Study. Issue 11 (1st November 2002) - Bolger, P M; Egan, K; Jensen, E; Canady, R
Abstract : The assessment presented in the core paper of this debate by Schafer and Kegley does not adequately describe the computational methodology or sources of data that were used to estimate exposures. While it is difficult to determine from the article, the exposure estimates seem to be very dependent on action levels, rather than on empirically derived data. There is no adequate presentation of analytical methods, limits of detection, or the significance of non-detects in deriving estimates of exposure.